2020
DOI: 10.1002/csc2.20232
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic optimal plant density for semiupright cowpea as a second crop in southeastern Brazil

Abstract: Cowpea [Vigna unguiculata (L.) Walp.] cultivars with high yield potential and suitable plant architecture for mechanized harvesting have recently shown a growing interest to be cultivated as a second crop in fall–winter season of southeastern Brazil. The agronomic optimal plant density (AOPD) is one of the main management factors defining attainable yield. However, in the scientific literature for semiupright cowpea cultivars grown in fall–winter season in southeastern Brazil the AOPD is not yet clearly define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In soybean, over a range of lower densities, from 7 to 29 plants per m 2 , HFP raised by 4.1 cm (from 10 to 14.1 cm), respectively, in one cultivar in Turkey (Öz, 2008), and from 10 to 35 plants per m 2 , HFP was increased either from 6.4 to 10 cm or from 10 to 12.5 cm, respectively, in two soybean cultivars studied in the United States (Epler and Staggenborg, 2008). Similar results were reported for cowpea and chickpea, where a density increase from 4.5 to 22.5 and from 20 to 50 plants per m 2 was accompanied by higher HFP, from 10 to 45 cm, in one cultivar of cowpea grown in Brazil (Soratto et al, 2020), from 19.9 to 21.9 cm and from 22 to 27.1 cm in Desi and Kabuli ecotypes of chickpea studied in Canada (Gan et al, 2003a,b), respectively. At higher densities, from 30 to 90 plants per m 2 , HFP was increased from 9.4 to 13.4 cm on average in four soybean cultivars in Germany (Sobko et al, 2019).…”
Section: Effect Of Environment Management and Treatment On Height To ...supporting
confidence: 79%
“…In soybean, over a range of lower densities, from 7 to 29 plants per m 2 , HFP raised by 4.1 cm (from 10 to 14.1 cm), respectively, in one cultivar in Turkey (Öz, 2008), and from 10 to 35 plants per m 2 , HFP was increased either from 6.4 to 10 cm or from 10 to 12.5 cm, respectively, in two soybean cultivars studied in the United States (Epler and Staggenborg, 2008). Similar results were reported for cowpea and chickpea, where a density increase from 4.5 to 22.5 and from 20 to 50 plants per m 2 was accompanied by higher HFP, from 10 to 45 cm, in one cultivar of cowpea grown in Brazil (Soratto et al, 2020), from 19.9 to 21.9 cm and from 22 to 27.1 cm in Desi and Kabuli ecotypes of chickpea studied in Canada (Gan et al, 2003a,b), respectively. At higher densities, from 30 to 90 plants per m 2 , HFP was increased from 9.4 to 13.4 cm on average in four soybean cultivars in Germany (Sobko et al, 2019).…”
Section: Effect Of Environment Management and Treatment On Height To ...supporting
confidence: 79%
“…(2016) also observed that less dense plant populations promoted the best absolute growth rate and relative growth rate values. The reduced leaf area resulted from dense plant population also decreased the photosynthetically active area, reducing radiation interception and then carbohydrate production which compromises plant DM accumulation (Feng et al., 2009; Soratto et al., 2020; Yao et al., 2016). Such results were verified here as the net assimilation rate was lower in the close‐spaced plant arrangements than the traditional layout (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, it was observed that competition between castor plants cultivated in dense populations, especially early growing season, can favor the emergence of unproductive plants and decrease seed production (Soratto et al., 2012). Likewise, competition between cowpea plants ( Vigna unguiculata L.) later in the season was found to reduce seed weight (Soratto et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A similar remote sensing approach has been used to predict LAI and its spatio-temporal evolution for bamboo (Xing et al, 2019) and other forests (Naithani et al, 2013;Schraik et al, 2019). For agronomical models of the LAI of food crops such as rice (Xu et al, 2019), Brazilian Cowpea (Soratto et al, 2020) or white winter wheat (Qu et al, 2008), local multispectral measurements are often used instead of-or in addition to-satellite images. In most of these studies, Bayesian hierarchical models are used to impose prior domain knowledge, combine multimodal data sources, and integrate data collected at multiple resolutions of space and/or time, all of which ultimately improve prediction performance.…”
Section: Introductionmentioning
confidence: 99%